ARTHROSCOPIC TREATMENT OF EQUINE FULL-THICKNESS CHONDRAL DEFECTS WITH CONSTRUCTS OF COLLAGEN ENCAPSULATED CELLS - Lombardero, G; Velasquillo, C; Aburto, E; Villegas, H; Morales, E; Masri, M; Martínez, V; Gómez, R; Chávez, T; Ibarra, C (Ecosistemas y Recursos Agropecuarios, 2014)
A full-thickness chondral defect in the stifle joint of eight mares was treated by perforation of the subchondral bone. In addition, the experimental group received an arthroscopic implant of a tissue-engineered construct. The objective was the arthroscopic evaluation of the quality of the repair tissue, six months after the treatments. The experimental group presented a statistically significant (p = 0.001) improvement in the repair tissue.